Mother Earth Needs a Band-Aid! Facts about Global Warming - Nature Books for Kids Children's Nature Books - Baby Professor (London, United Kingdom Baby Professor, 2017)
Global warming is the Earth's way of telling us that it's sick. A hole has started to appear in the atmosphere and if we don't act on it, it'll just keep getting bigger and the world will keep getting hotter too. This book will make global warming a child-friendly read to empower kids to do their share in helping the environment.
Keywords: Climate Action; Global Issues -- Global Issues; Environment Issues -- Environment Issues